Anthias albofasciatus Fowler and Bean, 1930, a junior synonym of Tosana niwae Smith and Pope, 1906 (Teleostei: Serranidae: Anthiadinae) - Gill, Anthony C.; Anderson, William D. Jr; Williams, Jeffrey T. (Zootaxa, 2019)
Anthias albofasciatus Fowler & Bean, known only from the holotype collected east of Hong Kong in the South China Sea, has been considered a valid species of either Anthias or Pseudanthias. The holotype is compared with the holotype of Tosana niwae Smith & Pope from Urado Bay, Shikoku, Japan, as well as non-type specimens from the South China Sea and south-eastern Japan, and shown to be conspecific. Anthias albofasciatus is therefore considered a junior subjective synonym of Tosana niwae.